Drug prescribing pattern in acute gastroenteritis in an in-patient setting in a private hospital - Bhaveshaikh, Nachiket; Sukumaran, Sangita; Vyas, Upal (International Journal of Research in Medical Sciences, 2017)
Background: Diarrheal diseases cause significant morbidity in developing countries and are the leading cause of death in children. The study was undertaken to assess drug utilization patterns in patients with gastroenteritis in a private setting. Methods: The in-patient data records of 208 patients (96 males, 112 females) admitted with acute gastroenteritis in a private hospital in Mumbai over 2 years were analysed. WHO core drug prescribing indicators - average number of drugs per prescription, percentage of drugs prescribed by generic name, percentage of encounters resulting in prescription of an antibiotic, percentage of encounters resulting in prescription of an injection were assessed. Patient demographics and trends in use of antibiotics, antiemetics and antidiarrheals were assessed. Results: The average total number of drugs prescribed per patient was 6.33 and average number of antibiotics was 1.61. 99% of drugs were prescribed using brand names. Percentage of encounters resulting in prescription of injection was 97.11%. Cephalosporins were the most commonly used group of antimicrobials (62.5%) followed by fluroquinolones (49.03%) and antiamoebic drugs (35.58%). Diphenoxylate was the most commonly prescribed antidiarrheal drug and ondansetron was the most commonly prescribed antiemetic agent. Cephalosporins were the most commonly used antimicrobials in patients diagnosed with enteric fever. Conclusions: Emperical irrational use of antibiotics was observed. There was paucity of stool culture for identification of causative agents. Review of antibiotic susceptibility patterns needs to be done on a regular basis. Educational programmes to reinforce the need for ORS and zinc supplementation are necessary.